Hoe ons Nederland een groen hart kreeg en het ook weer verloor - Kooij, P. (BMGN - Low Countries Historical Review, 2006)
Pim Kooij, The Green Heart of the Netherlands. A transient inventionAround 1960 in the Netherlands the ‘Green Heart’ was invented: this was the name given to a vast area of polders, cleared peat areas, ponds and villages, on the borders of the Randstad; a conurbation in the west of the Netherlands. Up until this point, there had been little appreciation for this type of manmade landscape, but now it became the icon of the Dutch green area. At the same time, however, the area became the focus of a bitter dispute because real estate developers, businessmen, politicians etc. were eager to start building activities. They launched a campaign to win the support of the general public for the idea of fragmenting the Green Heart area. By 2000 they had achieved their goal. This article is part of the special issue 'Landschap, natuur en nationale identiteit'.